Cost of arterioveinous fistula at the Douala General Hospital: A Cameroon-based cross-sectional study - Ngatchou Djomo William; Ivan Jutcha; Zakariou Njoumeni; Charles Mve Mvondo; Félicité Kamdem; Samuel Ndjoh; Marcel Johne; Junette Metogo; Marie Solange Ndom; Joseph Sango; Carole Ngo Nyom; Moulium Sidick; et al. (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2022)
Background: Cost is a major limiting factor for dialysis in low-income countries. The objective of our study was to determine the economic cost of creating an arteriovenous fistula (AVF) for hemodialysis at the Douala General Hospital (DGH). Material and methods: We conducted a descriptive cross-sectional study including patients undergoing AVF creation at the DGH from January to April 2020. Costs were calculated using a bottom-up approach. The direct cost was composed of the sum of the cost of medical consultation, additional paraclinical tests, drugs, disposables, hotel services, food, transport and medical and nursing care. The indirect cost was calculated as the sum of the costs related to the temporary incapacity to work and the additional expenses of the families. The cost of temporary work incapacity was calculated according to human capital theory. The economic cost was the sum of the direct cost and the indirect cost. The costs were expressed as a mean with standard deviation. The calculated costs were expressed in US Dollars. Statistical significance was considered as p < 0.05. Results: A total of 44 patients were included of which 29/44 (65.9%) were male. The mean age of the study population was 49.1 ± 14.7 years. The median monthly income was $172 and only 6.8% of patients had health insurance. The average direct cost per patient was $327.3 ± $212.7, with hospitalization costs accounting for 59.6% of that cost. The average indirect cost per patient was $64.5 ± $50.3. The largest proportion of these costs was due to lost productivity related to temporary work disability (45.7%). The average economic cost per patient was $391.9 ± $219.5. Direct costs accounted for 83.54% of the economic cost. Re-operation (p = 0.039), age (p < 0.01) and number of hospitalization days (p < 0.01) significantly affected the cost Conclusion: The cost of creating an AVF for hemodialysis was high and represented more than 2 times the median monthly income of patients and was mainly due to hospitalization costs. Therefore, there is a need to implement strategies to reduce the financial burden of arteriovenous fistula creation in our setting.